Aldudeko eta Luzaideko paperak eta gutunak, euskaraz idatziak - Ibarra Murillo, Orreaga (Huarte de San Juan. Filología y Didáctica de la Lengua, 2012)
Some letters found in Valcarlos and Aldude, written in Basque. In this article we gloss and summarise some letters found in two places. The first one is from Mezkiritz, and it’s written in Aldude. It is a receipt written at the end of the XIXth century. The rest of letters are more recent and they deal with the relationship between people from Valcarlos and their relatives from either the USA or France. Both of them constitute some scarce illustrations of written Basque in the Low-navarrese area.
Keywords: Luzaide; Aldude; letters; written Basque